Schott's almanac 2006 - Schott, Ben (Bloomsbury, 2005)
Schott's Almanac redefines the traditional almanac to present a record of the year just past and a guide to the year to come. It is designed to be a practical and entertaining volume that tells the real stories of the year, from the winner of UK's I'm a Celebrity Get Me Out of Here! to the distribution of income across the social spectrum, from the Asian Tsunami and its aftermath to Live8 and the crisis of the referenda on the European constitution, and from the death of the Pope to the trial of Michael Jackson.